Effectiveness of a brief intervention for smoking cessation using the 5A model with self-help materials and using self-help materials alone: A randomised controlled trial - Utap, Maurice Steve; Tan, Christina Phoay Lay; Ting, Anselm Su (Academy of Family Physicians of Malaysia, 2019)
Introduction: The '5A' model for smoking cessation was introduced in 2000 by the US Department of Health and Services. This brief intervention was recommended worldwide for smoking cessation. However, little is known about its effectiveness for smoking cessation in a primary care setting in Malaysia. Objective: To determine the effectiveness of a brief intervention for smoking cessation using the '5A' model with self-help materials compared to using self-help materials alone. Methods: This randomised controlled trial was conducted at the Primary Care Clinic at the University Malaya Medical Centre (UMMC) between June and October 2009. Subjects were all current smokers aged 18 years and above. A total of 208 subjects were recruited and randomised into two groups. Subjects in the intervention group were given a brief intervention based on the '5A' model with self-help materials, while the control group received self-help materials alone. Subjects were later followed up at one and four months via telephone calls. The outcome measure was a self-reported attempt to quit smoking. Results: At one-month follow-up, 15/77 (19.5%) of the participants in the intervention group had attempted to quit smoking compared to 8/80 (10.0%) in the control group. There was no significant difference between the two groups (p=0.09). At the four-month follow-up, 13/58 (22.4%) participants in the intervention group had attempted to quit smoking compared to 9/57 (15.8%) in the control group. Once more, there was no significant difference between the two groups (p=0.37). Conclusion: This study showed that there was no significant difference between a brief intervention using the '5A' model with self-help materials and using self-help materials alone for smoking cessation in a Malaysian primary care setting. However, these results do need to be treated with caution when taking into consideration the high dropout rate and bias in the study design. © 2019 Academy of Family Physicians of Malaysia. All rights reserved.